Thyroxine Transport in Thyrotoxicosis and Hypothyroidism - Inada, Mitsuo (1967)
(a) The thyroxine-binding proteins were investigated in 23 cases of untreated thyrotoxicosis and 16 cases of untreated hypothyroidism, employing reverse flow paper electrophoresis with the glycine acetate system at pH 8.6 in the Durrum type cell. (b) In active thyrotoxicosis, all sera exhibited diminished thyroxine-binding prealbumin (TBPA) capacities. however, 17 of the 23 sera also had diminished thryroxine-binding alpha globulin (TBG) capacities, as well as markedly elevated free thyroxine fractions. In contrast, six thyrotoxic sera had normal TBG capacities and normal or slightly elevated free thyroxine fractions. (c) In hypothyroidism, the TBPA capacities showed no consistent deviation from the normal range. 11 of the 16 sera had elevated TBG capacities as well as markedly diminished free thyroxine fractions. In contrast, five hypothyroid sera had normal TBG capacities and normal or nearly normal free thyroxine fractions. (d) In thyrotoxicosis and hypothyroidism, the inverse correlation between free thyroxine fraction and TBG was much closer than that with TBPA. When diagnostic categories were considered separately, only TBG bore a significant inverse relation to the free thyroxine fraction. It is therefore suggested that in thyroid diseases TBG may sometimes play a more important role than TBPA in determining the free thyroxine fraction. (e) The demonstrated variations in the binding proteins were considered sufficient to explain the abnormalities of the free thyroxine fractions in thyroid disease.